Obesity's Influence on Operative Management of Pediatric Supracondylar Humerus Fractures. Issue 3 (March 2018) - Li, Neill Y.; Bruce, William J.; Joyce, Cara; Decker, Norman M.; Cappello, Teresa
Abstract : Background: As childhood obesity remains an ongoing issue for the United States there has been an increasing number of studies detailing its effect on fracture complexity, management, and outcomes. This study utilizes a national database to examine whether obese children with supracondylar humerus fractures are more likely to require open reduction and internal fixation than nonobese children. Methods: The Healthcare Cost and Utilization Project Kid's Inpatient Database of 2003, 2006, 2009, 2012 were queried for pediatric supracondylar humerus fractures [International Classification of Disease (ICD-9), 812.41] between 2 and 12 years. Patients were separated into those undergoing closed reduction percutaneous pinning (CRPP), open reduction internal fixation (ORIF), or both. Obesity was determined by comorbidity and ICD-9 coding (ICD-9, 278.00, 278.01). Univariable and multivariable logistic regression models were utilized with P <0.05 considered significant. Results: Between 2003 and 2012, 31, 905 patients between the ages of 2 and 12 years sustained supracondylar humerus fractures. In total, 105 patients (0.3%) were obese. A majority of patients, 27, 658 (86.7%), underwent CRPP. Odds for ORIF increased in association with age, obesity, white race, and private insurance. Significant association was found between age and obesity ( P <0.05) in those undergoing ORIF. Obese children between 2 and 7 years of age had no difference in ORIF or CRPP compared with normal-weight children. Those between 8 and 12 years who were obese were significantly more likely to undergo ORIF (OR, 4.29; 95% confidence interval, 1.78-10.36). Conclusions: Supracondylar humerus fractures sustained in obese children between 8 and 12 years are over 4 times more likely to require ORIF compared with normal-weight children of the same age. Providers should identify and counsel older obese children and their families regarding the potential for increased difficulty in fracture management that may require open surgical intervention. Level of Evidence: Level IV—case series.